Effect of oxidation on the damping behavior of 2D C/SiC composites. (April 2015) - Zhang, Qing; Cheng, Lai-fei; Wang, Fu-yuan; Zhang, Li-tong
Abstract : A carbon fiber preform was chemical vapor infiltrated with a pyrocarbon (PyC) interphase and a SiC matrix, and then coated with a SiC outer layer by chemical vapor deposition to prepare 2D C/SiC composites with a density of 2.1 g/cm 3 . The composites were oxidized at 700, 1000, 1300 °C for 2, 5 and 10 h, respectively. The damping behavior of the oxidized composites was measured by a dynamical mechanical analyzer and the microstructural damage produced by the oxidation was investigated by scanning electron microscopy. Results show that the damping of the composites oxidized at 700 °C and 1000 °C increases initially and then decreases with increasing oxidation time while that of the composites oxidized at 1300 °C is independent of the oxidation time.The damping capacity of the C/SiC composites is determined by the carbon fibers, PyC interphase, SiC matrix and their interaction. The oxidation of the composites increases the damping by weakening the interfacial bonding due to the oxidation of PyC during the initial stage of oxidation, and decreases the damping by the oxidation loss of carbon fibers and excessive damage of the PyC interphase during the latter stages of oxidation. SiO2 formed at 1300 °C by the oxidation of SiC fills the voids produced by carbon oxidation, which increases the damping and compensates for the decrease of damping produced by carbon loss and excess damage of the PyC interphase. [New Carbon Materials 2014, 29(6): 522–528]